Revealing Relationship of Approaches of Learning STEM, ‎Learning Self-efficacy and Source of STEM Learning Self‎-efficacy Among International School Learners - Yue, Wong Seng; Hussain, Azham; Saare, Multaja Ali; Kamal, Fazillah Mohmad (International Journal of Basic and Applied Sciences, 2025)
STEM education plays an important role in producing more STEM-capable graduates for the future development of a nation. However, the ‎reduced number of science-stream learners at the secondary and tertiary levels in recent years is a huge concern. The enhancement of STEM ‎initiatives and, variety of strategies to support learners in STEM education have been carried out by the government. The scarce interest among ‎learners and the decline in learners’ abilities to study STEM have highlighted the importance of learners’ learning self-efficacy and their approaches ‎to learn STEM to determine this issue. Further, sources of self-efficacy (SSE) are the prerequisites to develop learners’ self-efficacy (SE). ‎Thus, this research attempts to examine the connection among learners’ SE, source of STEM learning self-efficacy (STEM SE), and ‎their approaches to learn STEM. There are 83 international secondary school learners invited to participate in this study. They have ‎participated in the outreach activities, which aim to motivate them to learn STEM and towards STEM. They have participated in this survey ‎study after the STEM outreach activities. This study points up the significance of socio-cultural factors and approaches during learners’ ‎development of their STEM SE, specifically the important roles played by the prominent factors. Inferences are reported to reduce learners’ ‎stress and sustain their self-efficacy for increasing their interest in STEM learning‎.
Keywords: Approaches of Learning; Self-Efficacy; Sources of Self-Efficacy; STEM Learning